EVALUATION OF STANDARD GIBBS POTENTIALS FOR COPPER HYDROXOSULFATE HYDRATES FROM SOLUTIONS OF DUAL LINEAR PROGRAMMING PROBLEMS - Yeriomin O.V.; Vinnichenko S.V.; Yurgenson G.A. (My University, 2006)
The study of an oxidation zone at the Udokan deposit has shown that alteration of copper sulfides (chalcopyrite, bornite, and chalcocite) under cryogenic conditions is accompanied by the formation of hydrated complex sulfates (hydroantlerite, hydrobrochantite, udokanite, fibroferrite, K-free jarosite, copper and iron sulfate pentahydrates, and others). No thermochemical data are available for these minerals. Optimization methods of calculation of geochemical equilibria make it possible to evaluate the thermodynamic functions of compounds. Let us use this possibility to calculate standard Gibbs energy of cryogenic copper hydroxosulfate hydrates.